Exploring the experiences and perspectives of Saudi mothers in interaction with their primary school children’s autonomy and motivation within COVID learning contexts - Boudy, Dheya (2025)
The COVID-19 pandemic impacted families worldwide; those in Saudi Arabia were among them. This period presented mothers with unique opportunities and challenges, including the chance to “get to know” their children better and explore strategies to promote autonomy and motivation during the primary school years. Despite Saudi Arabia’s ongoing development and implementation of Vision 2030 – i.e., a dynamic strategy that supports lifelong learning and individual potential – there is a notable lack of studies that focus on the role of the family and the importance of autonomy for children in remote learning. However, remote learning is a relatively new experience for Saudi society, especially for primary-aged children. This research aligns with the concept of “actualising tendency”, pioneered by Carl Rogers in 1961, which emphasises personal autonomy as an intrinsic motivation that drives individuals towards excellence. Understanding how Saudi families navigated these challenges during remote learning is crucial for children and future educational development and alignment with the goals of Vision 2030. This research is divided into two studies. The first study solely focuses on mothers with a background in Saudi Arabia; the second study concentrates on mothers with a multicultural “KSA-UK” background. In order to explore the mothers’ in-depth subjective experience with remote learning, an interpretative phenomenological analysis (IPA) is used to analyse the interview data and answer the following questions: 1. What experiences, challenges and strategies are encountered by Saudi mothers, with exposure to only a single culture, when their children interacted with remote learning? 2. What are the influential factors and strategies that Saudi mothers perceived and experienced when their children interacted with remote learning and multicultural contexts? The findings revealed a complex interplay of culture and mothers’ experiences, which seem to shape their self-concept, defined in this study as a person’s perception and comprehension of themselves, including their beliefs, values, abilities and traits (Ismail & Tekke, 2015). Furthermore, remote learning plays a role in collaboration between mothers and their children, allowing them to experience autonomy and self-determination. Mothers acknowledge their children’s ability to adapt to challenges in remote learning contexts, which seems to contribute to increasing child autonomy. In both studies, mothers used rewards and punishment as motivational methods, which presents tensions with the person-centred approach (PCA) and self-determination theory (SDT), as these approaches emphasise intrinsic motivation and the importance of fostering autonomy rather than relying on external controls such as rewards and punishments. The second study reveals how the mother’s experience abroad possibly influences her personal values and attitudes. Moving away may have disrupted the influence of others, allowing mothers more freedom to develop their parenting style. The findings are discussed in relation to previous research and relevant theories. The study also considers the implications of the findings for Saudi society and families, including Saudi mothers who study abroad, remote learning and childhood education.